Stabilization of the Elusive Antimony(I) Cation and Its Coordination Complexes with Transition Metals. (22nd October 2021) - Kumar, Vikas; Gonnade, Rajesh G.; Yildiz, Cem B.; Majumdar, Moumita
Abstract: Upon stabilization by 5, 6‐bis(diisopropylphosphino)acenaphthene to form compound 1, the fugitive antimony (I) cation exhibited nucleophilic behavior towards coinage metals. Compound 1 was strategically synthesized at room temperature from SbCl3, the bis(phosphine), and trimethylsilyl trifluoromethanesulfonate taken in a 1:2:3 ratio, whereby the bis(phosphine) plays the dual role of a reductant and a supporting ligand. The generation of 1 involves two‐electron oxidation of the ligand to form a P−P bonded diphosphonium dication. Compound 1 was separated from this dication to give both products in pure form in moderate yields. Despite the overall positive charge, the Sb I site in 1 was found to bind to metal centers, forming complexes with Au I, Ag I and Cu I . Compound 1 reduced Cu II to Cu I and formed a coordination complex with the resulting Cu I species. The effects of the electron‐rich bis(phosphine) and the constrained peri geometry in stabilizing and enhancing the nucleophilicity of 1 have been rationalized through computational studies. Abstract : The elusive Sb I cation has been stabilized by the 5, 6‐bis(diisopropylphosphino)acenaphthene ligand (see structure). The bis(phosphine) not only acts as a supporting ligand, but also enables the unique two‐electron reduction of the Sb III precursor in the presence of trimethylsilyl triflate, leading to Sb I cation. The strategically introduced nucleophilicity at the Sb I site enabled the first examples of its coordination to transition metals.